Optimizing a real-time PCR assay for rapid detection of Candida auris in nasal and axillary/groin samples. Issue 6 (1st June 2020) - Malczynski, Michael; Dowllow, Noor; Rezaeian, Saba; Rios, Javier; Dirnberger, Laura; Zembower, Jacob A.; Zhu, Alex; Qi, Chao
Abstract : Introduction . Candida auris is an emerging fungal pathogen. The organism can cause invasive infections associated with high mortality, has been implicated in outbreaks in healthcare settings and is frequently resistant to multiple antifungal agents, making it a significant challenge to infection prevention and patient treatment. Aim. To implement a real-time PCR assay for detection of C. auris in patient surveillance samples collected with the Copan Liquid Amies elution swab (ESwab) collection and transport system. Methodology. We optimized a real-time PCR testing procedure based on the sample collection device used in our institution. Results . ESwab transport medium was strongly inhibitory to the real-time PCR. Removing the medium with centrifugation, followed by suspending the pellet in PBS-BSA buffer (concentration 1 %), sufficiently eliminated the inhibition. The manual sample preparation method, freeze–thaw followed by mechanical disruption, allowed the detection of C. auris at the lowest cell concentration. Conclusion . The optimized procedure was used to test 1414 patient surveillance samples. The real-time PCR detected all culture-positive samples with 100 % sensitivity and 100 % specificity.